2009
DOI: 10.1080/07060660909507609
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of resistance components of bigleaf hydrangeas (Hydrangea macrophylla) toErysiphe polygoniin vitro

Abstract: Powdery mildew caused by Erysiphe polygoni is one of the major foliar diseases on bigleaf hydrangeas (Hydrangea macrophylla). To determine resistance components of bigleaf hydrangea to powdery mildew, fungal development and host necrotic cells were compared on six bigleaf hydrangea cultivars using a detached leaf disk bioassay. Germination percentages of conidia were not significantly different among cultivars. However, percent geminated conidia with secondary germ tubes (GCSGT), percent necrotic host cells, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
5
0
6
Order By: Relevance
“…macrophylla. Li et al (2009) observed high frequencies of necrotic cells in the leaves of 'Veitchii,' and these cells contributed to the inhibition of fungal growth, colony development, and sporulation. When 'Veitchii' and 'Bailmer' were crossed, they produced a new resistant cultivar 'Blushing Bride' in the F 1 generation.…”
Section: 7mentioning
confidence: 99%
See 2 more Smart Citations
“…macrophylla. Li et al (2009) observed high frequencies of necrotic cells in the leaves of 'Veitchii,' and these cells contributed to the inhibition of fungal growth, colony development, and sporulation. When 'Veitchii' and 'Bailmer' were crossed, they produced a new resistant cultivar 'Blushing Bride' in the F 1 generation.…”
Section: 7mentioning
confidence: 99%
“…Resistance screening. Resistance to powdery mildew in hydrangea cultivars has been assessed using pot-grown plants (Windham et al 2011) or detached leaves (Li et al 2009). Pot-grown plants were exposed to naturally occurring PM pressure, and the severity of PM on leaves was evaluated based on the percentage of foliage showing PM signs.…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation
“…La principal enfermedad foliar ocasionada por micopatógenos en esta planta, se conoce comúnmente como Oidiosis o ceniza (Li et al, 2018;Qiu, Braun, Li, & Li, 2019). En H. macrophylla se ha reportado que esta enfermedad puede ser ocasionada por micopatógenos del orden Erisiphales, y las especies que se reportan como agentes causantes de la Oidiosis son: (Li et al, 2009a(Li et al, , 2009bSchmidt & Scholler, 2011;Windham et al, 2011;Braun & Cook, 2012;Park, Cho, Park, Lee & Shin, 2012;Li et al, 2018;Qiu et al, 2019).…”
unclassified
“…Estos micopatógenos son parásitos biotrófos obligados que se desarrollan solo en las células epidérmicas y penetran a través de la cutícula por hifas especializadas llamadas apresorios. A partir de los apresorios se forman los haustorios, que le permiten al micopatógeno la absorción de agua y nutrientes (Li et al, 2009a(Li et al, , 2009bKuhn et al, 2016;Li et al, 2018).…”
unclassified